Contamination Measurement Techniques in Hydraulic Fluid Based on Hall Effect Sensor - Sutham Satthamsakul; Rojanee Khummongkol (My University, 2024)
This paper proposed two methods to examine metal particles in fluid using Hall Effect Sensor under the condition of nondestructive testing based on two conditions: test of particles in oil samples, and test of particles in industrial machinery simulation. Hall Effect Sensor was a low-cost device had ability to detect magnetic fields in objects, so this work applied Hall Probe to measure the density of metal in liquid. Hereby, hydraulic liquid was selected to examine because it was one of the most use in industrial machines. By using the sensor, two types of experiment were designed: test of oil sample, and test of simulation process, where the results showed that Hall Effect Sensor had ability to measure particles in both two types of experiment. For oil sample test, the sensor was able to detect metallic powder when the number of contaminants were greater than or equal to 10 milligrams (equivalented to NAS 15 standard). On the other hand, to measure particle in simulation process, magnetic field were generated in two ways, i.e. use of electromagnet, and use of permanent magnet. For using electromagnet as magnetic field source, the result showed that temperature had an influence on metal particle evaluation. Therefore, to get the most accurate value, system’s temperature had to employed in calculation process. While, the result of using permanent magnet to generate magnetic field showed that the relationship between output voltage and amount of metal particles were probably in linear form. To apply this method in industrial applications could be an inexpensive way to help officer in detecting metal particle in oil which was able to extend service time of hydraulic liquid properly.
Keywords: Magnetic Field Sensors Techniques; Sensor Technology and Measurement Systems